2017
DOI: 10.1371/journal.pone.0187857
|View full text |Cite
|
Sign up to set email alerts
|

Multiple effects of toxins isolated from Crotalus durissus terrificus on the hepatitis C virus life cycle

Abstract: Hepatitis C virus (HCV) is one of the main causes of liver disease and transplantation worldwide. Current therapy is expensive, presents additional side effects and viral resistance has been described. Therefore, studies for developing more efficient antivirals against HCV are needed. Compounds isolated from animal venoms have shown antiviral activity against some viruses such as Dengue virus, Yellow fever virus and Measles virus. In this study, we evaluated the effect of the complex crotoxin (CX) and its subu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 62 publications
1
27
0
1
Order By: Relevance
“…The development of efficient antiviral therapies has become a global health emergency. In this sense, several researches have demonstrated the antiviral activity of sPLA 2 s from snake venom against human viruses, including DENV, YFV, HCV and others [ [88] , [89] , [90] , [91] , [92] ]. Hence, the present review aimed to summarize the sPLA 2 s from snake venom that were previously described to possess antiviral activity, highlighting the mechanisms of action of sPLA 2 s against different stages of virus replication cycle ( Table 1 ).…”
Section: Phospholipases a 2 From Snake Venommentioning
confidence: 99%
See 4 more Smart Citations
“…The development of efficient antiviral therapies has become a global health emergency. In this sense, several researches have demonstrated the antiviral activity of sPLA 2 s from snake venom against human viruses, including DENV, YFV, HCV and others [ [88] , [89] , [90] , [91] , [92] ]. Hence, the present review aimed to summarize the sPLA 2 s from snake venom that were previously described to possess antiviral activity, highlighting the mechanisms of action of sPLA 2 s against different stages of virus replication cycle ( Table 1 ).…”
Section: Phospholipases a 2 From Snake Venommentioning
confidence: 99%
“…In order to gain insights into the antiviral mechanism of sPLA 2 s obtained from C. t. terrificus , Shimizu and colleagues [ 90 ] showed that PLA 2 -CB inhibited HCVcc JFH-1 virus strain entry and replication in Huh 7.5 cells, and crotoxin blocked virus entry and release, suggesting that these proteins possess multiple antiviral effects against HCV. Moreover, the authors also reported that PLA 2 -CB significantly decrease the levels of lipid droplets, which are essential for the HCV replication complex, and reduced the levels of HCV NS5A protein due to the replication inhibition, evidencing that besides the action on virus entry, PLA 2 -CB is able to disrupt HCV replication probably by an interference in lipid metabolism of host cell [ 90 , 100 , 101 ].…”
Section: Spla 2 S From Snake Venom With Antiviral mentioning
confidence: 99%
See 3 more Smart Citations